The Effect of Parents Digital Literacy on Sharenting Practices and Children’s Privacy on Instagram - Rapikah Harnum; Janette Maria Pinariya (Communicare : Journal of Communication Studies, 2023)
The development of technology has given rise to various social media platforms, suxh as Instagram. Instagram offers numerous features to its users for content creation, such as Instagram stories, feeds, Instagram reels, and live Instagram. The use of social media is closely related to digital literacy skills. Social media has a significant impact on society, including changes in parenting patterns, known as "sharenting." Sharenting refers to the activity of parents sharing photos or videos of their children's growth and development on social media, which often makes it difficult to restrict their lives on social media and their children's privacy. This study aims to investigate the influence of parents' digital literacy on their sharing behavior and their children's privacy. The research utilizes a quantitative method by conducting a survey with 400 respondents. The findings of the study reveal that digital literacy has a significant influence on sharenting, with a coefficient of 0.799, a t-statistic of 16.785, and a p-value of 0.000. This indicates that digital literacy has a proven positive and significant impact on sharenting. Furthermore, digital literacy also has a positive and significant influence on children's privacy, as the coefficient of digital literacy's influence on children's privacy is 0.774, with a t-statistic of 16.059 and a p-value of 0.000.